2016
DOI: 10.1371/journal.pone.0163817
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia Coexists with Cancer Related Anemia and Adversely Impacts Quality of Life

Abstract: Cancer related anemia (CRA) adversely affects patient Quality of Life (QoL) and overall survival. We prospectively studied the prevalence, etiology and the impact of anemia on QoL in 218 Indian cancer patients attending a tertiary referral hospital. The study used the sTfR/log Ferritin index to detect iron deficiency anemia and assessed patient QoL using the Functional Assessment of Cancer Therapy-Anemia (FACT-An) tool, standardized for language. Mean patient age was 51±13 years and 60% were female. The preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 27 publications
0
30
1
1
Order By: Relevance
“…Similar findings have also been reported by Kanuri G et al they reported that when patients were categorized according to the type of cancer, the mean hemoglobin value was lowest in patients with a diagnosis of lymphoma followed by lung cancer, GI tumors and cancer of head and neck. There were no demonstrable differences in mean hemoglobin values based on patients cancer stage in their study, this can be attributed to the fact that most of the patients in their study were in stage IV at the time of diagnosis [11]. Wu Y et al [12] also observed patients with hematologic malignancies were more likely to have anemia at the time of diagnosis, the next highest prevalence for anemia was 53.3% among patients with breast cancer, and 50.9% among patients with non-small cell lung cancer (NSCLC).…”
Section: Discussionmentioning
confidence: 63%
“…Similar findings have also been reported by Kanuri G et al they reported that when patients were categorized according to the type of cancer, the mean hemoglobin value was lowest in patients with a diagnosis of lymphoma followed by lung cancer, GI tumors and cancer of head and neck. There were no demonstrable differences in mean hemoglobin values based on patients cancer stage in their study, this can be attributed to the fact that most of the patients in their study were in stage IV at the time of diagnosis [11]. Wu Y et al [12] also observed patients with hematologic malignancies were more likely to have anemia at the time of diagnosis, the next highest prevalence for anemia was 53.3% among patients with breast cancer, and 50.9% among patients with non-small cell lung cancer (NSCLC).…”
Section: Discussionmentioning
confidence: 63%
“…7 As far as distribution of Hb level is concerned among all cancer patients, 87.56% patients were having Hb level more than 9gm% and around 12.43% patients were having Hb level less than 9 gm%. Majority of patients whose Hb level was less than 9gm% were belonging to age group more than 45 years.…”
Section: Discussionmentioning
confidence: 95%
“…Iron status of cancer patients should be closely monitored as the incidence of anemia could compromise greatly their quality of life 44 . Current finding showed that higher quality diet was associated with reduced risk of low serum hemoglobin only after adjusting for physical activity and BMI (Model 2), suggests that diet quality might indirectly improve anemia by reducing excess body weight.…”
Section: Discussionmentioning
confidence: 99%